The Implementation of the Discretion of the Contracting Authority while Terminating a Public Contract for a Material Breach - Soloveičik, Deividas (Teisė, 2020)
This publication is a scholarly research on two separate yet interconnected legal categories: the discretion of the contracting authorities in public procurement and their right to use a unilateral termination of the public contract for the material breach as a remedy. The author hereby contends that there is a two-phase test which must be used in each case when the question of discretion arises. Moreover, the author believes that the latter cognitive tool must be implemented during the both at the time of the procurement procedures and amid the execution of the public contract. The author also argues that the provisions of the Civil Code must not be solely referred to in cases of termination of a public contract and that the procurement principles must always be deployed alongside to make a rational decision regarding the exit of the public contract.
Keywords: public procurement; contracting authority; discretion; public contract; termination of the contract